2016
DOI: 10.1371/journal.pone.0154202
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behaviours to Antimicrobial Prescribing following Introduction of a Smartphone App

Abstract: ObjectivesOur hospital replaced the format for delivering portable antimicrobial prescribing guidance from a paper-based pocket guide to a smartphone application (app). We used this opportunity to assess the relationship between its use and the attitudes and behaviours of antimicrobial prescribers.MethodsWe used 2 structured cross-sectional questionnaires issued just prior to and 3 months following the launch of the smartphone app. Ordinal Likert scale responses to both frequencies of use and agreement stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 9 publications
2
54
0
3
Order By: Relevance
“…The mechanisms to measure and describe the utility of such mHealth interventions should be multimodal, and sensitive enough to measure the added value in the context of multiple interventions aimed at maximizing outcome measures. We would advocate integrating quantitative measures such as those presented here with qualitative criteria such as increased access to the policy at the point of care, the reach of the policy to healthcare professionals and the feedback from users 15 , 21 . In this study, the addition of the antimicrobial prescribing policy as an mHealth app to a multifaceted ASP did not demonstrate a significant change in antimicrobial prescribing trends.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanisms to measure and describe the utility of such mHealth interventions should be multimodal, and sensitive enough to measure the added value in the context of multiple interventions aimed at maximizing outcome measures. We would advocate integrating quantitative measures such as those presented here with qualitative criteria such as increased access to the policy at the point of care, the reach of the policy to healthcare professionals and the feedback from users 15 , 21 . In this study, the addition of the antimicrobial prescribing policy as an mHealth app to a multifaceted ASP did not demonstrate a significant change in antimicrobial prescribing trends.…”
Section: Discussionmentioning
confidence: 81%
“…Both studies show that the health professionals found apps useful and relevant to their patient population. They also agreed that apps encouraged them to challenge inappropriate prescribing [ 6 ]. The concern displayed by healthcare workers for the emergence of drug-resistant infections and the use of the standard treatment guidelines as seen in Table 6 was highly impressive.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent rise in the use of smartphones generally across global population and it is predicted to be rising fastest in Africa. There has been increased development of smartphone apps designed for use in healthcare, including in the area of antimicrobial stewardship [ 3 , 4 , 5 , 6 , 7 ]. Current research in medicine has shown that the use of mobile phones and devices in medical settings is more popular and is increasingly being brought to the fore of international research [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPRF can take many forms but is invariably both human resource and time intensive. Many hospitals may lack the resources to initiate this level of stewardship universally [3,4], and there is therefore a need to identify the form of PPRF that most efficiently impacts inappropriate antimicrobial prescribing [5,6]. We performed a prospective, observational study that compared different forms of PPRF: ward round reviews on acute medical wards, ward round reviews on surgical recovery wards, and telephone reviews with clinical teams caring for patients receiving carbapenems, cephalosporines, or quinolones.…”
Section: Time Efficiency Assessment Of Antimicrobial Stewardship Stramentioning
confidence: 99%